Genetic diversity study of guava (Psidium guajava) for pink pulp and soft seededness - Thakre, Madhubala; Asrey, Ram; Singh, Awtar; Ray, Mrinmoy; Jha, S K; Kumar, Puneet; Saha, Supradeep; Sharma, Khushbu; Awasthi, Aakansha; Goswami, Amit Kumar; Nagaraja, A (The Indian Journal of Agricultural Sciences, 2020)
India is one of the largest guava (Psidium guajava L.) producing country. This exotic crop adapted very well to climatic condition of nation which results in its huge variability in the form of seedling population. In present investigation the existing genetic diversity of guava explored and analyzed on the basis of physico-chemical characters during 2015-16 at Sawai Madhopur district of Rajasthan (India). The objective was to find some pink pulped and soft seeded guava genotypes. Among 17 guava genotypes, a wide range of diversity was recorded with respect to fruit weight (74.45-357.29), fruit length (45.6-93.96 mm), fruit diameter (50.70-86.15 mm), TSS (7.9-16.3Â°B), acidity (0.26-0.77%), ascorbic acid (52.44-164.86 mg/100 g) and lycopene content (3.53-6.18 mg/100 g). Seed variables like hardiness (44.06-132.98 N), length (2.22-3.96 mm) and width (1.85-3.16 mm), number of seeds per fruit (99-775) and seed index (0.17-1.48) also exhibited variability. However, highest coefficient of variation was found for fruit weight (52%) and ascorbic acid content (41.1%). Fruit weight was observed to be positively and significantly correlated with fruit diameter, fruit length, peel thickness, seed core thickness, seed hardness and seed weight. Titrable acidity was positively correlated with seed length, seed width and seed index. Four genotypes, viz. BKDV, JSL2, IFA and RFJ were identified for further multiplication to establish them at the Germplasm Block for their detailed evaluation and utilization in the breeding programme.